Students 'Speaking Through Extracurricular Reading - Surmaxon Ismoilova (Genius Journals, 2022)
The article expands the horizons of human thinking through reading books, plays an important role in finding a worthy place, respect and attention in society, the book is a friend, constant companion, inexhaustible wealth for every self-conscious believer, thousands of years of research and discoveries of our ancestors. Show that their thoughts and feelings are sealed. Therefore, it is stated, one of the urgent issues is to pay special attention to the issue of arousing interest in fiction among young schoolchildren and expand the scope of work carried out in the field of reading. Extracurricular reading lessons have a great opportunity to develop students ’oral speech. One of these opportunities is to tell the content of the book you are reading. We can use this type of extracurricular reading not only in elementary grades but also in later grades
Keywords: Research; Discovery; Personality; Mature